Pengaruh Kualitas Pelayanan Terhadap Loyalitas Debitur Kredit Produktif (Studi pada Kantor Cabang BNI SKC Malang) - Putra, I Wayan Jaman Adi (Universitas Brawijaya, Indonesia, 2012)
The objectives of the research are to know: (1) the situation of service quality (tangible, empathy,reliability, responsiveness, assurance) of bank which perceived by customer of BNI productive credit andcustomer loyalty of BNI productive credit; (2) the influence of situation of service quality on the customerloyalty. The sources of data are all customers of BNI productive credit at branch offices of BNI Small CreditCentre which offered BNI productive credit in marketing area of Malang City. The election of 110 respondentsthat are planned uses simple random sampling technique and allocated proportionally, the methodsof collecting data are questionnaire, interview, and slider of document. The methods of analysis are: (1)descriptive analysis; and (2) hypothesis testing by Structural Equation Modeling (SEM).The results ofdescriptive analysis are: (1) Totally the level of situation of service quality (tangible, empathy, reliability,responsiveness, assurance) of bank which perceived by customer of BNI productive credit is very higheffectiveness category, but dissatisfied category; (2) Totally, the level of customer loyalty to BNI productivecredit is high sufficient category. (3) The results of hypothesis testing is the situation of service quality(tangible, empathy, reliability, responsiveness, assurance) of bank which perceived by customer are influencingpositively and significant on the customer loyalty of BNI productive credit.